A new model for understanding global media and China: 'Knowledge clubs' and 'knowledge commons'. Issue 1 (March 2017) - Hartley, John; Montgomery, Lucy; Siling Li, Henry
The topic of this article and title of this journal are the same: 'global media and China'. Although 'global' suggests a single universal unit, adding 'China' necessarily creates a difference, especially in the context of the 'Great Firewall', which creates a well-defined boundary between global media and China. Should our title read 'Global Media versus China', suggesting that the apparent universality of 'global' phenomena may be an illusion in a world marked by difference? We argue the contrary: that difference, produced along borderlines between different cultures – defined as those sociocultural groups whose boundaries require translation to cross, rather than simple transmission – is the productive energy that generates new knowledge (and thence, innovation) among large populations. We show that the peculiarity of current relations between global media and China is not evidence of exceptional 'Chinese characteristics', but of how culture deals with the globalisation of communication, and consciousness of that process among whole populations.